Pengaruh Diskon, Brand Image, dan Kemudahan Akses terhadap Keputusan Pembelian Mahasiswa Pengguna Aplikasi Shopee Melalui Minat Beli sebagai Variabel Intervening - Christovao Natalio Hasto T.X.S, Christovao Natalio Hasto T.X.S (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study analyzes the Effect of Discounts, Brand Image, and Ease of Access on the purchasing decisions of students using the Shopee application through buying interest as an intervening variable. This study aims to examine the influence of discounts, brand image, and ease of access to purchasing decisions through buying interest. This research was conducted on 100 respondents using the Shopee application on students. Data was collected by distributing questionnaires with a scale of 1-5 points to measure indicators. The analytical technique used in this research is to use descriptive analysis.